A Novel Experimental Approach for In Vivo Analyses of the Salivary Gland Microvasculature - Uhl, Bernd; Braun, Constanze; Dominik, Julian; Luft, Joshua; Canis, Martin; Reichel, Christoph A. (Frontiers in Immunology, 2021)
Microvascular dysfunction plays a fundamental role in the pathogenesis of salivary gland disorders. Restoring and preserving microvascular integrity might therefore represent a promising strategy for the treatment of these pathologies. The mechanisms underlying microvascular dysfunction in salivary glands, however, are still obscure, partly due to the unavailability of adequate in vivo models. Here, we present a novel experimental approach that allows comprehensive in vivo analyses of the salivary gland microvasculature in mice. For this purpose, we employed different microscopy techniques including multi-photon in vivo microscopy to quantitatively analyze interactions of distinct immune cell subsets in the submandibular gland microvasculature required for their infiltration into the surrounding parenchyma and their effects on microvascular function. Confocal microscopy and multi-channel flow cytometry in tissue sections/homogenates complemented these real-time analyses by determining the molecular phenotype of the participating cells. To this end, we identified key adhesion and signaling molecules that regulate the subset- and tissue-specific trafficking of leukocytes into inflamed glands and control the associated microvascular leakage. Hence, we established an experimental approach that allows in vivo analyses of microvascular processes in healthy and diseased salivary glands. This enables us to delineate distinct pathogenetic factors as novel therapeutic targets in salivary gland diseases.